Manipulation of cellular spheroid composition and the effects on vascular tissue fusion. (February 2015) - Olsen, T.R.; Mattix, B.; Casco, M.; Herbst, A.; Williams, C.; Tarasidis, A.; Simionescu, D.; Visconti, R.P.; Alexis, F.
Abstract : Graphical abstract: Abstract: Cellular spheroids were investigated as tissue-engineered building blocks that can be fused to form functional tissue constructs. While spheroids can be assembled using passive contacts for the fusion of complex tissues, physical forces can be used to promote active contacts to improve tissue homogeneity and accelerate tissue fusion. Understanding the mechanisms affecting the fusion of spheroids is critical to fabricating tissues. Here, manipulation of the spheroid composition was used to accelerate the fusion process mediated by magnetic forces. The Janus structure of magnetic cellular spheroids spatially controls iron oxide magnetic nanoparticles (MNPs) to form two distinct domains: cells and extracellular MNPs. Studies were performed to evaluate the influence of extracellular matrix (ECM) content and cell number on the fusion of Janus magnetic cellular spheroids (JMCSs). Results showed that the integration of iron oxide MNPs into spheroids increased the production of collagen over time when compared to spheroids without MNPs. The results also showed that ring tissues composed of JMCSs with high ECM concentrations and high cell numbers fused together, but exhibited less contraction when compared to their lower concentration counterparts. Results from spheroid fusion in capillary tubes showed that low ECM concentrations and high cell numbers experienced more fusion and cellular intermixing over time when compared to their higher counterparts. These findings indicate that cell–cell and cell–matrix interactions play an important role in regulating fusion, and this understanding sets the rationale of spheroid composition to fabricate larger and more complex tissue-engineered constructs.